The Crutchley Archive: Red Colours on Wool Fabrics from Master Dyers, London 1716–1744. (2nd July 2020) - Quye, Anita; Cardon, Dominique; Paul, Jenny Balfour
Abstract : The Crutchley Archive is a rare book collection with over a thousand dyeing instructions and colourful dyed patterns from an eighteenth-century wool fabric dyeing business in Southwark, London, owned by John Crutchley and his family. Our research of the outstandingly detailed dyeing materials and methods by text study, dyed textile history, dye analysis and colorimetry reveals unprecedented insight for 'in grain' and 'out of grain' dyeing of medium to high quality wool fabric using cochineal, stick lac, madder and other dyes, and shows the dyers to be skilled colourists. Other novel discoveries are instructions translated from Flemish or Old Dutch into English, a range of dyed patterns with broadcloth 'lists' (distinctive selvedges) and monogrammed dyeing calculations. Customer cash transactions were from 5 s to £2, 586. This research has resulted in UNESCO Memory of the World Programme recognition of the Crutchley Archive as significant documentary heritage for UK textile history.